2014
DOI: 10.1155/2014/846021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation and Neutrophil Activation as Possible Causes of Joint Diseases in Ballet Dancers

Abstract: Herein, we investigated the effects of a ballet class on the kinetic profiles of creatine kinase (CK) and lactate dehydrogenase (LDH) activities, cytokines, complement component 3 (C3), and the concentrations of immunoglobulin (Ig), IgA and IgM, in ballerinas. We also verified neutrophil death and ROS release. Blood samples were taken from 13 dancers before, immediately after, and 18 hours after a ballet class. The ballet class increased the plasma activities of CK-total (2.0-fold) immediately after class, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The authors suggested that due to degenerative remodeling occurring during the development of OA, these complexes become structurally and functionally impaired, resulting in increased access of exogenous ADP to mitochondria and dysfunction of the CK-phosphotransfer system. Borges et al (29) identified increased plasma activities of total CK (2.0-fold) in ballet dancers immediately after class, a finding that is significant in preventing the development of chronic conditions that are commonly observed in dancers, such as those with arthritis and synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that due to degenerative remodeling occurring during the development of OA, these complexes become structurally and functionally impaired, resulting in increased access of exogenous ADP to mitochondria and dysfunction of the CK-phosphotransfer system. Borges et al (29) identified increased plasma activities of total CK (2.0-fold) in ballet dancers immediately after class, a finding that is significant in preventing the development of chronic conditions that are commonly observed in dancers, such as those with arthritis and synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…A standard curve was constructed for each sample and cytokine set assayed, yielding correlation coefficients from 0.98 to 0.99. For these experiments, the intra‐assay coefficient of variance was 3–5%, while the interassay coefficient of variance was 8–10% .…”
Section: Methodsmentioning
confidence: 99%
“…The available literature on biomonitoring studies comprising professional dancers is limited, and the evaluation of genotoxic effects encompassing these professionals is even scarcer. Borges et al (2014) investigated the effect of chronic inflammation and neutrophil activation including neutrophils DNA fragmentation (an apoptosis biomarker) in 13 ballerinas from a ballet class. Blood samples were taken from dancers before, immediately after and 18 hr after class, a significant elevation was found in neutrophils DNA fragmentation 18 hr after class compared to pre-class and immediately after class, illustrating an impact of intense physical exercise on cytogenetic markers after a ballet class.…”
Section: Discussionmentioning
confidence: 99%
“…Although oxidative responses among different sport athletes were reported in several studies (Hadžović-Džuvo et al, 2014 ;Marin et al, 2013;Rowlands et al, 2012), only few studies measured DNA damage (Borges et al, 2014;Orhan et al, 2004). Borges et al (2014) investigated the effects of a ballet class in 13 ballerinas on DNA fragmentation by flow cytometry and found a significant increase 18 hr after ballet class. Orhan et al (2004) evaluated the effect of 60 min on a cycle ergometer in 18 trained males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation